2007
DOI: 10.1177/1096348007299920
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Educational Mismatch and Labor Mobility in the Hospitality Industry

Abstract: The aims of this article are to analyze the determinants of educational mismatch and worker mobility across occupations and firms in the hospitality industry. The educational mismatch is measured comparing the worker's maximum level of attained education and the educational level needed to perform his or her job. A representative survey of 3,314 employees and 302 employers in 181 hotels and 121 restaurants with 8 employees or more was utilized to this end. The econometric analyses suggest that workers can comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 42 publications
3
40
0
2
Order By: Relevance
“…In addition, real educational mismatch has a limited effect on the probability of changing jobs within the firm. This result is in line with previous literature, which found no evidence to suggest that overeducated workers obtain better jobs in other establishments or that either gender benefits from promotion ladders within internal labour markets (Marchante et al, 2007). Thus, entry positions do not serve as first step in the workers' future career within this sector.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In addition, real educational mismatch has a limited effect on the probability of changing jobs within the firm. This result is in line with previous literature, which found no evidence to suggest that overeducated workers obtain better jobs in other establishments or that either gender benefits from promotion ladders within internal labour markets (Marchante et al, 2007). Thus, entry positions do not serve as first step in the workers' future career within this sector.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, external mobility among women does not have a positive effect on rewards. These results are in line with those obtained by Marchante et al (2007) for the Spanish hospitality sector. They found that the most important reason workers changed firms was to improve their working conditions (61% of total quits) rather than to raise their wages (23% of the total quits).…”
Section: Internal Mobilitysupporting
confidence: 94%
See 3 more Smart Citations